Dietas mediáticas de adultos mayores peruanos para informarse, educarse y entretenerse: estudio exploratorio - Dr. Julio-César MATEUS,Mg. Giancarlo CAPPELLO,Dr. Lizardo VARGAS-BIANCHI (Fonseca, Journal of Communication, 2023)
This article explores the media diets of the elderly population over 60 years old in Peru, based on a nationwide panel study. Studies that address this age group are scarce and limited to examining audiences. To fill this gap, our research characterizes the use, motivations, and expectations of older adult media users. The final sample consists of 145 cases distributed by gender, socioeconomic level, and geographical location from across the country